Efficacy of artificial insemination in Holstein and Jersey cattle, considering necessary attempts for financial return on investment - Bastos, Guilherme Pepino; Androukovitch, João Luiz; Machado, Ângelo José Penna (Revista de Ciências Agroveterinárias, 2025)
The technique of artificial insemination is one of the most important biotechnologies ever conceived for genetic improvement in production animals. Making it possible to increase the number of offspring of a single sire and to use semen after their death or reproductive inaptitude. However, females that have difficulties or do not conceive with the use of the technique generate more costs for the properties. It is justified to evaluate the ideal number of attempts on a female, before transferring her to natural breeding or disposal. The objective of this study was to evaluate the conception rates of cattle breeders from two rural properties, in order to analyze the factors involved and stipulate a number of adequate attempts to generate pregnancy, based on the relationship of costs and benefits, through the generation of mathematical formulas. This study was done with a total of 108 animals from two rural properties, of which 59 (54.6%) became pregnant after the first artificial insemination, 18 animals (16.7%) had pregnancy confirmed after the second and 14 animals (13%) after the third. The three replications result in a pregnancy rate of 84.3%, a result close to the ideal 85%. Finally, it can be concluded that establishing calculation bases involving the largest number of variables possible along with indicators of return on investment and return on investment period can help in the management of rural properties, as it can reveal the real situation of the activity and its operations.